Engaged in integrated reporting? Evidence across multiple organizations. Issue 4 (11th June 2018) - Lopes, Ana Isabel; Coelho, Ana Margarida
Abstract : Purpose: The purpose of this paper is twofold: to provide evidence on geographic and firm-level characteristics within organizations using integrated reporting () methodology to communicate their business model to stakeholders; and to shed light on the contend of integrated reports of organizations that have been recognized as leading practice by a reputable award process or through benchmarking. Design/methodology/approach: Secondary analysis of data (descriptive and inferential statistics) is used for a sample of 224 organizations (79 classified as Reference Reporters and 145 as Regular Reporters) across 26 countries (2011 to mid-2015). Content analysis is used for Reference Reporters. Findings: Evidence for the first objective suggests that compared with Regular Reporters, the majority of the Reference Reporters are from Europe, are larger, have a higher market value, are more profitable and are less leveraged. Evidence for the second objective reveals that the guiding principles, fundamental concepts and content elements of the most recent integrated report published by each Reference Reporter (leading practice) seem less than expected. Research limitations/implications: Examples Database does not cover all of the organizations reporting according to the framework. Content analysis can be biased by authors' interpretations. Practical implications: Potential benefit both to researchers and to those involved in the reporting of financial and non-financial information using the tool. Originality/value: The originality of the paper is as follows: it contributes to the international debate on the evolution from sustainability to, provides evidence on geographies and firm-level characteristics of organizations using to better communicate and provides the most prominent information disclosed by Reference Reporters.